En Femenino: Del hombre pintor/artista a la feminización del arte prehistórico - Inés Domingo (Munibe Antropologia-Arkeologia)
La investigación sobre arte prehistórico ha experimentado una notable evolución en clave de género. Las teorías que durante décadas atribuyeron exclusivamente a los hombres el papel de pintores/artistas y la capacidad artística, y que presentaban a las mujeres simplemente como modelos, están siendo reemplazadas por enfoques de género más inclusivos. Estos enfoques utilizan el arte prehistórico como un medio para reivindicar la presencia femenina en la Prehistoria, y también su participación como autoras y consumidoras del arte. Desde una perspectiva histórica, este giro femenino está íntimamente ligado al impacto de los movimientos feministas en la investigación arqueológica a partir de la década de 1970, así como al aumento del protagonismo de las mujeres en la investigación. Este artículo analiza esta evolución y sintetiza los debates actuales sobre las mujeres y el arte prehistórico y los desafíos que conlleva rastrear su presencia. ABSTRACT: Research on prehistoric art has experienced a significant transformation over time, incorporating gender perspectives, and reshaping research questions in more critical, engaged, and inclusive ways. Theories, long unquestioned, that for decades exclusively attributed artistic roles and abilities to men, while relegating women to the role of mere models, are being replaced by more gender-inclusive approaches. These new approaches use prehistoric art (and particularly the presence of female representations in rock art and portable art) to argue the presence of women in prehistory, as well as their participation as both creators and consumers of art. From a historical perspective, this feminist turn is closely tied to the impact of feminist movements on archaeological research from the 1970s onwards. The significant rise in the presence of women in scientific and academic circles, along with the feminization of research topics, the adoption of innovative methods to determine the biological identity (sex and age) of individuals involved in the creative process (such as morphometric analysis of hands and dermal patterns of fingerprints), new ethnographic approaches that incorporate gender perspectives, and insights drawn from the archaeological context of the art are collectively contributing to a more inclusive rewriting of the history of prehistoric art. This article examines this development and provides an overview of the current debates surrounding women and prehistoric art, as well as the challenges involved in tracking their presence. The paper concludes by noting that while the presence of women in prehistoric art reflects their presence not only in prehistory but also in the symbolic realm of prehistoric societies, using these images to infer the roles of men and women in prehistoric times is problematic. Such interpretations venture into the realm of speculation and should, therefore, be approached with caution.